SPEOS (Stimulation of Endorphin, Oxytocin and Suggestive): Intervention to Improvement of Breastfeeding Production (Medico Legal Update, 2019)
Background: The problem of preliminary breast milk expenditure that is not yet smooth is often the reason for the mother to delay or replace it with breast milk substitutes. Even though they have obtainedearly breastfeeding initiation, the expenditure and production of breast milk are not yet smooth.Objectives: Proving the SPEOS method (Stimulation of Endorphin, Oxytocin,and Suggestive) is effective against increasing breast milk production.Method: The study used a quasi-experimental pre and posttest design. The sample was 60 postpartum mothers in the Mojokerto area hospital who met the research criteria, taken with a simple random sampling technique. The control group gets early breastfeeding initiation according to the procedure. The intervention group was given the SPEOS method (Stimulation of Endorphin, Oxytocin and Suggestive) intervention method, which was carried out according to the procedure. Assessment of breast milk production is carried out by pumping breast milk, using Pigeon (ml) pumps. Data collection used a weighing test for breast milk production. Processing and analysis of data used paired t-test, Mann Whitney test,and LSD test.Result: The SPEOS method affected the increase in breast milk production. There were significant differences in the production of breast milk pre-post control group, obtained t-count 8.923 (p = 0.000) and the experimental group t-count 18.886 (p = 0.000). The difference in the level of comfort between groups with the LSD test obtained p-value = 0.035.Conclusion: The findings of the study show that the SPEOS method (Stimulation of Endorphin, Oxytocin,and Suggestive) is one of the alternative interventions for increasing milk production and accelerating the release of breast milk through increased work of prolactin and oxytocin.